INVESTIGATION OF THE SPATIAL GENOME ORGANIZATION OF MOUSE SPERM AND FIBROBLASTS BY THE Hi-C METHOD - N. R. Battulin; V. S. Fishman; A. A. Khabarova; M. Yu. Pomaznoy; T. A. Shnaider; D. A. Afonnikov; O. L. Serov (Вавиловский журнал генетики и селекции)
The spatial organization of an eukaryotic genome plays an important role in the control of nuclear gene expression. The new Hi-C method allows investigation of the three-dimensional architecture of whole genomes. It has not been applied to study of the spatial configuration of a germ cell genome hitherto. Here we describe a protocol for production and quality control of Hi-C libraries from fibroblasts and sperm cells. Our results demonstrate that the Hi-C method can be used for studying the spatial organization of the densely packed sperm genome.